Qualitative and quantitative evaluation of computed tomography changes in adults with cystic fibrosis treated with elexacaftor-tezacaftor-ivacaftor: a retrospective observational study - Dettmer, Sabine; Weinheimer, Oliver; Sauer-Heilborn, Annette; Lammers, Oliver; Wielpütz, Mark O.; Fuge, Jan; Welte, Tobias; Wacker, Frank; Ringshausen, Felix C. (Frontiers in Pharmacology, 2023)
Introduction: The availability of highly effective triple cystic fibrosis transmembrane conductance regulator (CFTR) modulator combination therapy with elexacaftor–tezacaftor–ivacaftor (ETI) has improved pulmonary outcomes and quality of life of people with cystic fibrosis (pwCF). The aim of this study was to assess computed tomography (CT) changes under ETI visually with the Brody score and quantitatively with dedicated software, and to correlate CT measures with parameters of clinical response. Methods: 22 adult pwCF with two consecutive CT scans before and after ETI treatment initiation were retrospectively included. CT was assessed visually employing the Brody score and quantitatively by YACTA, a well-evaluated scientific software computing airway dimensions and lung parenchyma with wall percentage (WP), wall thickness (WT), lumen area (LA), bronchiectasis index (BI), lung volume and mean lung density (MLD) as parameters. Changes in CT metrics were evaluated and the visual and quantitative parameters were correlated with each other and with clinical changes in sweat chloride concentration, spirometry (percent predicted of forced expiratory volume in one second (ppFEV1)) and body mass index (BMI). Results: The mean (SD) Brody score improved with ETI (55 (12) vs. 38 (15); p<0.001), incl. sub-scores for mucus plugging, peribronchial thickening, and parenchymal changes (all p<0.001), but not for bronchiectasis (p=0.281). Quantitatve WP (p<0.001) and WT (p=0.004) were reduced, conversely LA increased (p=0.003), and BI improved (p=0.012). Lung volume increased (p<0.001), and MLD decreased (p<0.001) through a reduction of ground glass opacity areas (p<0.001). Changes of the Brody score correlated with those of quantitative parameters, exemplarily WT with the sub-score for mucus plugging (r=0.730, p<0.001) and peribronchial thickening (r=0.552, p=0.008). Changes of CT parameters correlated with those of clinical response parameters, in particular ppFEV1 with the Brody score (r=-0.606, p=0.003) and with WT (r=-0.538, p=0.010). Discussion: Morphological treatment response to ETI can be assessed using the Brody score as well as quantitative CT parameters. Changes in CT correlated with clinical improvements. The quantitative analysis with YACTA proved to be an objective, reproducible and simple method for monitoring lung disease, particularly with regard to future interventional clinical trials.